Lexicographica : International Annual for Lexicography / Revue Internationale de Lexicographie / Internationales Jahrbuch für Lexikographie (De Gruyter, 1985)
Published annually since 1985, this international yearbook covers all topics in the field of lexicography, including e.g. dictionary making, lexicographic theory, the history of lexicography, as well as computational lexicography. It publishes articles on monolingual and bilingual lexicography, for both general language and specialized languages. Each yearbook contains a thematic part with detailed articles selected from a specific call.